Cross-cultural validation of the decisional balance scale in exercise across countries - Kueh, Yee Cheng; Sabo, Abdulwali; Kim, Youngho; Kuan, Garry (PloS one, 2021)
Background This study examined the psychometric properties of the Korean and Malay version of the decisional balance (DB) for exercise (i.e. perceived benefits and perceived barriers) using a cross-sectional design. Also, this study assessed the measurement and structural invariance of the DB scale across countries. Methods A cross sectional study was conducted in Malaysia and Korea. The study sample consisted of 574 Korean participants and 562 Malaysian participants. The mean age of the participants was 19.8 (SD = 1.29) for the Korean sample and 19.8 (SD = 1.22) for the Malaysian sample. Participants were invited to complete the DB scale with the 10-item and two factors (i.e., perceived benefit and perceived barriers). Confirmatory factor analysis (CFA) and invariance test were conducted on the data by using Mplus 8.3. Results The CFA results based on the hypothesised measurement model of two factors and ten items showed sufficient construct validity after adding residual covariance between items within the same factor: CFI = 0.979, TLI = 0.970, SRMR = 0.036, RMSEA = 0.036 for the Korea sample, and CFI = 0.964, TLI = 0.949, SRMR = 0.055, RMSEA = 0.066 for the Malay sample. For the Korea sample, the construct reliability was 0.62 and 0.74 for perceived benefits and perceived barriers respectively. For the Malay sample, the construct reliability was 0.75 and 0.77 for perceived benefits and perceived barriers respectively. The findings presented evidence for measurement and structural invariance of the DB scale for the Korea and Malaysia samples. Conclusion The DB scale was a valid and reliable measure for assessing exercise behaviour and for making comparisons between Korean and Malaysian samples.